2019
DOI: 10.1021/acs.jpca.9b06628
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio/Transition-State Theory Study of the Reactions of Ċ5H9Species of Relevance to 1,3-Pentadiene, Part I: Potential Energy Surfaces, Thermochemistry, and High-Pressure Limiting Rate Constants

Abstract: In this study, the reactions of Ċ5H9 radicals are theoretically investigated, with a particular emphasis on hydrogen atom addition reactions to 1,3-pentadiene (C5H8) to form Ċ5H9 radicals, although the subsequent isomerization and decomposition reactions of the Ċ5H9 radicals are also of direct relevance to the radicals formed from the pyrolysis and oxidation of species including pentene and cyclopentane. Moreover, H-atom abstraction reactions by hydrogen atoms from 1,3-pentadiene are also investigated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…As discussed above in Methods, we model the pore space of deAl-BEA by using DFT to compute properties of molecule I in all-silica MOR, which contains channels very similar in size to those of BEA. Regarding guest species I , it has been reported that molecules of this nature exist in either s-cis or s-trans conformations, , prompting us to begin by investigating the equilibrium between the two conformers using computed Gibbs and Helmholtz energies, and the impact of these conformers on the IR spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above in Methods, we model the pore space of deAl-BEA by using DFT to compute properties of molecule I in all-silica MOR, which contains channels very similar in size to those of BEA. Regarding guest species I , it has been reported that molecules of this nature exist in either s-cis or s-trans conformations, , prompting us to begin by investigating the equilibrium between the two conformers using computed Gibbs and Helmholtz energies, and the impact of these conformers on the IR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Dienes such as molecule I have a dihedral angle along the single bond in between the two C=C bonds, resulting in two stable conformations denoted as s-trans and s-cis, where the ‘s’ indicates torsion around the s ingle bond. Previous reports on substituted dienes suggest that the s-trans conformer can be lower in energy by as much as 3 kcal/mol, thus exhibiting higher population at thermal equilibrium. , We investigated the thermodynamic stabilities of conformers of I by computing free energy profiles for the s-cis and s-trans conformers in vacuum and over all-silica MOR (Table S1 in Supporting Information). Interestingly, we found that a gauche s-cis conformation of I has lower free energies than its s-trans counterpart at 20 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this work is to develop comprehensive kinetics for the title reaction for use in a detailed chemical kinetic model describing C 5 species oxidation. Ḣ atom addition reactions to the pentadiene isomers and cyclopentene have been extensively studied theoretically and literature papers describing the Ċ 5 H 9 PES have been documented in part I of this study . Moreover, the thermochemistry of the C 5 species used in this study has been comprehensively validated against literature data in part I.…”
Section: Introductionmentioning
confidence: 96%
“…As highlighted in part I of this study, olefins and dienes are important intermediates generated via heavy petroleum cracking. The reactions of Ċ 5 H 9 radicals have an important effect on the performance of a C 5 combustion mechanism and may also influence the combustion chemistry of larger dienes and alkenes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation